Literasi Informasi Kesehatan Mental Pada Siswa/I Smp It Aulia Muara Bulian - Rahim, Beny; Pramudiani, Dessy; Ekawati, Yun Nina; Iranda, Agung; Andriani, Annisa (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2025)
The period of Junior High School (SMP) is a time of transitional growth. At this age, students experience rapid development in psychological, physical, and cognitive aspects. One of the characteristic at this stage is a heightened curiosity about many things, a love for adventure and challenges, and a vulnerability to risky behaviors due to still immature thinking. At this age, they strive to find answers to their questions by seeking information from various sources. Currently, information can be easily accessed through a wide range of available resources. However, the prevalence of information from unreliable sources can create problems if readers, especially adolescents, are unable to discern the truth of the information they receive. Therefore, strong literacy skills are needed to evaluate and verify the information they read. However, many students still lack these literacy skills, highlighting the urgency of educating them about mental health information literacy. To address this issue, students need to be provided with understanding through psychoeducational programs about the importance of mental health information literacy from trustworthy sources. The evaluation of the program will be conducted by administering pretests and posttests to measure participant’s understanding. From the evaluation, most of the participants had higher posttest’s scores, indicating an increase in their knowledge about mental health literacy skill. They also participating actively in the psychoeducation session, indicating an interest in program’s topic. So it can be concluded that psychoeducation program about mental health literacy is effective for increasing student’s mental health literacy in cognitive and affective aspect.